Heat control in hard rock : TBM cutter interaction - Chng, Bryan Siyong (Nanyang Technological University, 2020)
The abrasivity of rocks is a major determining factor of the rate of cutter wear in a Tunnel Boring Machine, different rock treatment methods are being evaluated to see its effects on the cutter-rock interaction to reduce cutter wear. The aim of this study is to investigate how different cooling treatments on heated Bukit Timah granite samples affects its abrasivity. The Cerchar Abrasivity test is performed on Bukit Timah granite samples that were heated to temperatures of 200°C, 400°C, 600°C and then exposed to two types of cooling treatments, slow cooling and rapid cooling. Visual observations were made on the samples’ surface using an optical microscope after the cooling treatments to detect the changes that have occurred to the surface of the rock samples. The Cerchar Abrasivity test is then performed to observe the cooling treatment’s impact on the sample’s abrasivity. Acoustic Emissions testing were performed on the samples, to observe the internal structural effects that the treatments have on the samples. The investigation reveals that there is a decrease in the CAI values of the samples when subjected to the rapid cooling treatment as compared to the slow cooling treatment. Microscopic observations also shows that more extensive inter-granular cracking occurs at a lower temperature for rapidly cooled samples. The Acoustic Emissions test suggests that there are more internal cracks formed during the CAI test for the samples that were rapidly cooled. More in depth research is recommended to further improve the understanding of the effects of cooling treatments on Bukit Timah granite’s abrasivity.